2019
DOI: 10.7717/peerj.7328
|View full text |Cite
|
Sign up to set email alerts
|

Children’s attitudes towards animals are similar across suburban, exurban, and rural areas

Abstract: The decline in the number of hours Americans spend outdoors, exacerbated by urbanization, has affected people’s familiarity with local wildlife. This is concerning to conservationists, as people tend to care about and invest in what they know. Children represent the future supporters of conservation, such that their knowledge about and feelings toward wildlife have the potential to influence conservation for many years to come. Yet, little research has been conducted on children’s attitudes toward wildlife, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…Analyses of survey responses for both adults and youth indicated that NCCC participation enhanced wildlife knowledge, bolstered sense of place and connection to nature, and increased science efficacy (Pedrozo 2019). Similar wildlife camera trapping projects have been shown to increase environmental literacy, science efficacy, and conservation advocacy (Forrester et al 2017;Schuttler et al 2019). Collectively, these results provide evidence that our engagement efforts in NCCC led to significant broader impacts, and they accentuate the idea that citizen science can benefit both science and society (McKinley et al 2017).…”
Section: Engagement and Evaluationmentioning
confidence: 61%
“…Analyses of survey responses for both adults and youth indicated that NCCC participation enhanced wildlife knowledge, bolstered sense of place and connection to nature, and increased science efficacy (Pedrozo 2019). Similar wildlife camera trapping projects have been shown to increase environmental literacy, science efficacy, and conservation advocacy (Forrester et al 2017;Schuttler et al 2019). Collectively, these results provide evidence that our engagement efforts in NCCC led to significant broader impacts, and they accentuate the idea that citizen science can benefit both science and society (McKinley et al 2017).…”
Section: Engagement and Evaluationmentioning
confidence: 61%
“…Although the term nature-deficit disorder has been criticised for its part in medicalising childhood, it has been recognised that the process of alienation from the natural world at the heart of NDD has occurred incrementally over many generations (Dickinson 2016) and recent studies have confirmed the negative effects of such alienation on human well-being (see, for example , Miller 2005;Soga & Gaston 2016). For Stephanie Schuttler et al (2019) the problem of alienation is specifically related to people's disconnection from local wildlife and local biodiversity.…”
Section: Nature-deficit Disordermentioning
confidence: 99%
“…Pyle's contribution was to recognise that alienation from nature not only diminishes human well-being but can also lead to a cycle of further apathy in regard to environmental conservation, and 'therefore to further extinctions: a cycle of disaffection and loss, sucking the life out of the land the passion out of the people' (Pyle 2005, p. 398). As a consequence of this negative feedback loop, alienation from nature is one of the biggest threats to conservation of the planet's biodiversity (Schuttler et al 2019). At the heart of this problem, as Pyle sees it, is 'the epic level of our nature illiteracy, amounting to almost utter ignorance of species other than our own ' (2005, p. 400).…”
Section: Nature-deficit Disordermentioning
confidence: 99%
“…Notably, March Mammal Madness blends together four approaches to science outreach – gamification, social media platforms, community event(s), and creative products ( Subhash and Cudney, 2018 ; Varner, 2014 ; Bush et al, 2018 ) – with salient animal-based content. Science communicators have previously recognized that students in the United States are particularly interested in animal behavior ( Bush et al, 2018 ) across urban, suburban, and rural landscapes in which species diversity and visibility varies ( Schuttler et al, 2019 ). At very young ages, children are attracted to neotenous and familiar animal phenotypes ( Borgi et al, 2014 ; Borgi and Cirulli, 2015 ).…”
Section: Introductionmentioning
confidence: 99%